(untitled) (Multi-disciplinary Journal of Research and Development Perspectives, 2026)
Population constitute a very important resource for development and when it is managed well it can be a catalyst for any meaningful development. The FGN in its effort to control the rapidly growing population of Nigeria (2.5%) put in place a National Population Policy of Nigeria (NPPN) in 1988 and 2004 which stipulates four children per woman. This research is aimed at assessing the level of awareness of Nigerians of the policy and the extent to which they have complied. The research used the survey design and adopted 300 as the sample population and the method for collecting data was through questionnaire using the random sampling technique. The findings of the research revealed that 91.3% of the respondents are literate, 82% have ever heard of the NPPN and 70%, have 1-4 children. Most of the targets of the NPPN aimed at birth control have not been achieved by 2021. The researchers recommended that: efforts be made by government to sustain the progress made. An agency of government must be charged with the responsibility of sustaining awareness campaigns. Religious leaders should be involved in the awareness campaign. Adequate funding of the implementation agencies will form the bases for sustainability.